Os impactos urbanos na instalação de grandes empreendimentos: um estudo dos supermercados no município de Ribeirão Preto : o EIV como instrumento de gestão urbana - Stanganini, Fábio Noel (Universidade Federal de São Carlos, 2011)
This dissertation deals with the EIV - Neighborhood Impact Study in setting up business-generating impact, in this case, the supermarkets in the urban area of Ribeirão Preto - SP. The purpose of this dissertation is to present and observe the impacts generated by these businesses post-installation and their damages, whether temporary or permanent, caused by its surroundings and the urban context. Thus, we seek to integrate the establishment of enterprises and quality of urban life that can be achieved in communion with economic growth. Through the use of geo and field studies was done to conduct the dissertation. As a result, it was observed that the installation of supermarkets in urban areas is already consolidated the city and with a standard infrastructure to minimize impacts as parking, traffic generation, noise and others. Supermarkets are potential developments that impact, and these impacts can be minimized with neighborhood impact studies. It is emphasized that the ultimate goal of AI is the search for a combination of environmental and economic factors within the urban environment, not impeding or obstructing the construction, but rather giving technical and scientific support so that this instrument of urban management, help in shaping more sustainable cities.
Keywords: Planejamento urbano; Estudo de impacto de vizinhança; Meio ambiente urbano; Cidades médias; ENGENHARIAS